Intercomparison of arctic XH 2 O observations from three ground-based Fourier transform infrared networks and application for satellite validation - Q. Tu; F. Hase; T. Blumenstock; M. Schneider; A. Schneider; R. Kivi; P. Heikkinen; B. Ertl; C. Diekmann; F. Khosrawi; M. Sommer; T. Borsdorff; et al. (Atmospheric Measurement Techniques, 2021)
In this paper, we compare column-averaged dry-air mole fractions of water vapor ( XH 2 O ) retrievals from the COllaborative Carbon Column Observing Network (COCCON) with retrievals from two co-located high-resolution Fourier transform infrared (FTIR) spectrometers as references at two boreal sites, Kiruna, Sweden, and Sodankylä, Finland, from 6 March 2017 to 20 September 2019. In the framework of the Network for the Detection of Atmospheric Composition Change (NDACC), an FTIR spectrometer is operated at Kiruna. The H 2 O product derived from these observations has been generated with the MUlti-platform remote Sensing of Isotopologues for investigating the Cycle of Atmospheric water (MUSICA) processor. In Sodankylä, a Total Carbon Column Observing Network (TCCON) spectrometer is operated, and the official XH 2 O data as provided by TCCON are used for this study. The datasets are in good overall agreement, with COCCON data showing a wet bias of ( 49.20±58.61 ) ppm (( 3.33±3.37 ) %, R 2 =0.9992 ) compared with MUSICA NDACC and ( 56.32±45.63 ) ppm (( 3.44±1.77 ) %, R 2 =0.9997 ) compared with TCCON. Furthermore, the a priori H 2 O volume mixing ratio (VMR) profiles (MAP) used as a priori information in the TCCON retrievals (also adopted for COCCON retrievals) are evaluated with respect to radiosonde (Vaisala RS41) profiles at Sodankylä. The MAP and radiosonde profiles show similar shapes and a good linear correlation of integrated XH 2 O , indicating that MAP is a reasonable approximation of the true atmospheric state and an appropriate choice for the scaling retrieval methods as applied by COCCON and TCCON. COCCON shows a reduced dry bias ( −14.96 %) in comparison with TCCON ( −19.08 %) with respect to radiosonde XH 2 O . Finally, we investigate the quality of satellite data at high latitudes. For this purpose, the COCCON XH 2 O is compared with retrievals from the Infrared Atmospheric Sounding Interferometer (IASI) generated with the MUSICA processor (MUSICA IASI) and with retrievals from the TROPOspheric ...